2011
DOI: 10.1007/s00383-010-2823-y
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric surgery telehealth: patient and clinician satisfaction

Abstract: Telehealth for pediatric surgical services is an alternative as an acceptable, effective, and appropriate way to consult and follow-up pediatric patients who live in significantly remote areas with great clinician and patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 8 publications
4
49
0
Order By: Relevance
“…These data are consistent with other applications of telehealth that reveal high patient and provider satisfaction rates (e.g., Gustke et al, 2004;Abrams and Geier, 2006;Shivji et al, 2011). For example, in the Shivji et al (2011) study, 97% of participants reported satisfaction with receiving remote surgical consultations, and 73% of providers were satisfied with providing those remote services.…”
Section: Discussionsupporting
confidence: 81%
“…These data are consistent with other applications of telehealth that reveal high patient and provider satisfaction rates (e.g., Gustke et al, 2004;Abrams and Geier, 2006;Shivji et al, 2011). For example, in the Shivji et al (2011) study, 97% of participants reported satisfaction with receiving remote surgical consultations, and 73% of providers were satisfied with providing those remote services.…”
Section: Discussionsupporting
confidence: 81%
“…Use of videoconferencing technology for healthcare intervention and support has been widely tested in several disciplines, including cardiac health, surgical care, and disease management [16][17][18] but, to the authors' knowledge, this is the first published work exploring its application to remote lactation support. Results of the pilot work presented here indicate that acceptability of remote lactation consultation is likely to be quite high, though much work is still required.…”
Section: Discussionmentioning
confidence: 99%
“…More than 20,000 teleconsultations have been delivered by 37 different paediatric sub‐specialties . Similar paediatric telesurgical consultations are available in a number of Canadian provinces, and also in the USA . Given the rapid evolution of telecommunication and videoconferencing equipment, evidence supporting the accuracy of diagnosis at teleconsultation ought to be periodically assessed …”
mentioning
confidence: 99%
“…7,8 Similar paediatric telesurgical consultations are available in a number of Canadian provinces, and also in the USA. [9][10][11] Given the rapid evolution of telecommunication and videoconferencing equipment, evidence supporting the accuracy of diagnosis at teleconsultation ought to be periodically assessed. [10][11][12][13][14] Canadian provinces in particular face similar health-care access challenges to Queensland due to their geographical size, and the proportion of the population residing in regional areas.…”
mentioning
confidence: 99%